MAKING SKILL DEVELOPMENT CENTER AS BASIS FOR SUSTAINABLE ENTREPRENEURS EMPOWERMENT IN FACING CHANGES IN THE WORLD OF WORK - Afif Syarifudin Yahya; Saadah Oktaviani (International Journal of Economics and Management Research, 2022)
The government develops for citizens to get a job and decent living. Nevertheless, the number of people who are unemployed and poor is still high. To solve those problems, the government establish the Skills Development Center as a basis for sustainable entrepreneur empowerment. This research aims to analyze entrepreneurial empowerment activities at the Skills Development Center, their positive impact, the dominant factor influencing success, and the effort to optimize the success of the Skills Development Center in facing changes in the world of work. This research used a qualitative descriptive method with an inductive approach. Data collection was documentation, interviews, and observation. The informants were 11 people who were determined based on the purposive sampling technique. Data analysis techniques through reduction, display, and conclusion drawing verification. The results showed the stages of awareness, enabling, and empowerment in implementing entrepreneurial empowerment very well. The positive impact is success in increasing agricultural and livestock entrepreneurship. The dominant factors are government policy support, increased cooperation, and adequate human resources. At the same time, the barrier factors are low community participation and lack of budget support. Then, the effort to optimize care coordination, verification, and facilitation of training activities, coordination and cooperation among regional agencies, and increasing cooperation with the industrial world so that the type of entrepreneurship can be varied and competitive.